2020
DOI: 10.9734/ijtdh/2020/v41i330260
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Aqueous Leaf Extracts of Thymus schimperi and Moringa stenopetala on Regional Blood Flow Velocity and Vascular Resistance of Pre-eclampsia Rat Models

Abstract: Background: Pre-eclampsia (PE) is a common hypertensive disorder of pregnancy with a prevalence rate of 3-5%. There is no modern drug which cures PE so far. On the other hand, plant medicines are claimed to cure this disease. Exploring potential plant medicines for their therapeutic and/or prophylactic uses in this disease, therefore has paramount importance. In Ethiopia, there is a strong claim that leaves of Moringa stenopetala and Thymus schimperi have anti-hypertension activities. Thus, the current study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several studies have reported that Moringa stenopetala has hypotensive, antihyperlipidemic, and also has nutritional value [24][25][26][27]. Similarly, moringa extract has also shown a protective effect on the liver and kidney due to its protective action against lipid peroxidation and reactive oxygen species [28,29].…”
mentioning
confidence: 99%
“…Several studies have reported that Moringa stenopetala has hypotensive, antihyperlipidemic, and also has nutritional value [24][25][26][27]. Similarly, moringa extract has also shown a protective effect on the liver and kidney due to its protective action against lipid peroxidation and reactive oxygen species [28,29].…”
mentioning
confidence: 99%